Проникнення рідини в кулясту частинку, покриту нерозчинною полімерною оболонкою - Демчук, І.; Опанасович, В.; Слободян, М. (Видавництво Національного університету «Львівська політехніка», 2003)
We leaded to mathematical equation’s process and graphical alteration’s independence of concentration in particle and polymer membrane. This enable prognosis penetration’s time of solution in the particle.